A combination of humanized anti-BCMA and murine anti-CD38 CAR-T cell therapy in patients with relapsed or refractory multiple myeloma. Issue 6 (12th May 2022) - Zhang, Huan; Liu, Man; Xiao, Xia; Lv, Hairong; Jiang, Yanyu; Li, Xin; Yuan, Ting; Zhao, Mingfeng
Abstract: Chimeric antigen receptor T (CAR-T) cells are a promising approach in hematopoietic malignancies. We evaluated the safety and efficacy of a combination of humanized anti-BCMA and murine anti-CD38 CAR-T cell therapy in patients with relapsed or refractory multiple myeloma (R/RMM). Twenty-two R/RMM patients, with a median age of 56 years and a median number of previous therapies of 8, were included in the study. Both CAR-T cells infusion doses were 2.0 × 10 6 /kg. The overall response rate (ORR) was 90.9%, with 12 patients (54.5%) achieving a strict complete response/complete response (sCR/CR). The 24-month overall survival (OS) rate was 56.6%, and the progression-free survival (PFS) rate was 48.7%. Cytokine release syndrome (CRS) of grades 1–2 occurred in 16 patients (72.7%) and of grade ≥3 in six patients (27.3%). Immune effector cell-associated neurotoxic syndrome (ICANS) of grades 1–2 occurred in three patients (13.6%). The combination therapy is potential in R/RMM patients. Trial registration: The patients were enrolled in clinical trials registered as ChiCTR1800017051.